The short cytoplasmic region of phage T4 holin is essential for the transition from impermeable membrane protein complexes to permeable pores - Schwarzkopf, Jan Michel Frederik; Viveros, Ruth Paola; Burdur, Ali Nazmi; Mehner-Breitfeld, Denise; Tschowri, Natalia; Brüser, Thomas (Frontiers in Microbiology, 2025)
Virulent as well as temperate phages usually require lysis of bacteria to release their progeny into the surrounding. Double-stranded DNA phages achieve lysis by phage-encoded endolysins that degrade the bacterial cell wall. Endolysins cross the cytoplasmic membrane by the aid of phage-encoded hole-forming membrane proteins, the holins. Canonical holins have been shown to multimerize and form very large holes in membranes, and it is believed that these holes enable a non-specific release of endolysins from cytoplasm. We studied these aspects with Escherichia coli and the phage T4 model lysis system, consisting of the holin T and the endolysin E. By following the endolysin function in a microfluidic chamber with mEGFP-fused holin, we found that large multimerizations were not required for endolysin release. Moreover, while we found in further analyses of this construct that the periplasmic globular domain was not required for hole formation and thus likely serves only regulatory functions, the short cytoplasmic domain was essential for hole formation. A truncation as well as single point mutations abolished hole formation without affecting holin interactions. In agreement with this, AlphaFold 3 indicates that rings of holin T dimers can form aqueous holes that require a conformational switch of the N-terminal cytoplasmic amphipathic helix to a trans-membrane orientation inside the rings. Our data indicate that already small holin assemblies enable endolysin-mediated cell lysis, although large multimers may be formed in the absence of endolysins due to the clustering of such assemblies. Further, we provide a convincing structural model of a ring-shaped holin T complex that can form an aqueous pore of sufficient diameter to permit endolysin release.